Taking a strong interactional stance. (5th April 2023) - Förster, Frank; Broz, Frank; Neerincx, Mark
Abstract: We outline two points of criticism. Firstly, we argue that robots do constitute a separate category of beings in people's minds rather than being mere depictions of non-robotic characters. Secondly, we find that (semi-)automatic processes underpinning communicative interaction play a greater role in shaping robot-directed speech than Clark and Fischer's theory of social robots as depictions indicate.